2005
DOI: 10.1007/s00424-005-1478-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functional voltage-gated Na+ channels in cultured human pulmonary artery smooth muscle cells

Abstract: Electrical excitability, which plays an important role in excitation-contraction coupling in the pulmonary vasculature, is regulated by transmembrane ion flux in pulmonary artery smooth muscle cells (PASMC). This study aimed to characterize the electrophysiological properties and molecular identities of voltage-gated Na + channels in cultured human PASMC. We recorded tetrodotoxinsensitive and rapidly inactivating Na + currents with properties similar to those described in cardiac myocytes. Using RT-PCR, we det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 37 publications
1
35
0
1
Order By: Relevance
“…Others include voltage-gated Na + channel, T-type Ca 2+ channel, ClC-3 chloride channel, TRPC6 channel, inward rectifier K + channel, K V 3.4 channel and Na + -Ca 2+ exchange [20,[56][57][58][59][60][61][62][63]; conversely, loss of specific ion channels (e.g. K V 1.5) can also contribute [64].…”
Section: Changes In Other Aspects Of Ion Transportmentioning
confidence: 97%
“…Others include voltage-gated Na + channel, T-type Ca 2+ channel, ClC-3 chloride channel, TRPC6 channel, inward rectifier K + channel, K V 3.4 channel and Na + -Ca 2+ exchange [20,[56][57][58][59][60][61][62][63]; conversely, loss of specific ion channels (e.g. K V 1.5) can also contribute [64].…”
Section: Changes In Other Aspects Of Ion Transportmentioning
confidence: 97%
“…Moreover, vinpocetine is a potent voltage-gated sodium channel blocker (Bönöczk et al, 2000). The voltage-gated sodium channel has been found in several types of SMCs, and these channels seem to be important for SMC migration but not proliferation (Platoshyn et al, 2005;Meguro et al, 2009). Besides SMCs, the anti-inflammatory effects of vinpocetine on vascular cells and macrophages (Jeon et al, 2010b) may contribute to the inhibitory effects of vinpocetine in neointima formation.…”
Section: Vinpocetine Inhibits Pathological Vascular Remodeling 485mentioning
confidence: 99%
“…The physiological significance of increased Na + currents in proliferating cells remains a mystery. Platoshyn et al [109] showed evidence that increased Na + currents does not directly influence membrane potential, intracellular Ca 2+ release or proliferation in cultured human pulmonary artery smooth muscle. These authors speculated that increased Na + currents could contribute to activation of upregulated NCX in its reverse mode, leading to an increase of the bulk of cytoplasmic Ca 2+ and enhanced cell proliferation [109].…”
Section: Other Changes Involving Various Ion Channelsmentioning
confidence: 99%